Patterns of intracellular compartmentalization, trafficking and acidification of 5'-fluorescein labeled phosphodiester and phosphorothioate oligodeoxynucleotides in HL60 cells. - Tonkinson, J L (1994)
We have examined the intracellular compartmentalization and trafficking of fluorescein labeled (F) phosphodiester (PO) and phosphorothioate (PS) oligodeoxynucleotides (oligos) in HL60 cells. A series of F-oligos (PO and PS) were incubated for 6 hrs. with HL60 cells and the mean intracellular fluorescence determined by flow cytometry. The F signal was normalized by the addition of the ionophore monensin. An increase in signal intensity following addition of monensin indicated that the oligo was resident in an acidic intracellular environment. F-PS, but not F-PO oligos were found to reside in an acidic environment. An exception was a PO homopolymer of 15 cytidine bases (FOdC15) which was acidified. Using two different methods, the average resident intracellular pH of F-PS oligos and F-OdC15 was shown to be approximately 1 pH unit lower than that of F-PO oligos. Acidification of F-PS oligos could be blocked by the antibiotic bafilomycin, indicating that acidification was occurring in endosomes or vacuoles. F-PO and F-PS oligos were effluxed from HL60 cells from two intracellular compartments. However, approximately 60% of internalized F-PO oligo resided in a 'shallow' compartment that was turned over rapidly (t1/2 = 5-10 min.) whereas only 20% of F-PS oligo resided in this compartment. Conversely, approximately 80% of the internalized F-PS oligo but only 40% of F-PO oligo resided in a 'deep' compartment that turned over with t1/2 = 2-5 hrs. This report is the first quantitative demonstration that PO and PS oligos, and PO oligos of different sequences are trafficked differently by HL60 cells.